2010
DOI: 10.1055/s-0030-1270115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land-Based Neonatal Transport on Outcomes in Transient Tachypnea of the Newborn

Abstract: We sought to determine the effect of neonatal transport on the incidence of adverse events of transient tachypnea of the newborn (TTN) in term neonates. A retrospective study was performed of neonates who had TTN and were admitted to Neonatal Intensive Care Unit (NICU) of Sami Ulus Maternity, Children's Education and Research Hospital by land-based transport. Data from 208 newborns with TTN were evaluated, and clinical and laboratory findings were compared between patients who were transported from within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Male sex as a risk factor for pneumothorax is well established [5,7]. The evidence regarding the impact of outborn status on pneumothorax is conflicting [8,10,11]. Whereas CPAP was protective in early preterm neonates, CPAP was a risk factor for pneumothorax in moderate-late preterm and term neonates.…”
Section: Risk Factors For Neonatal Pneumothoraxmentioning
confidence: 99%
See 1 more Smart Citation
“…Male sex as a risk factor for pneumothorax is well established [5,7]. The evidence regarding the impact of outborn status on pneumothorax is conflicting [8,10,11]. Whereas CPAP was protective in early preterm neonates, CPAP was a risk factor for pneumothorax in moderate-late preterm and term neonates.…”
Section: Risk Factors For Neonatal Pneumothoraxmentioning
confidence: 99%
“…In term neonates, risk factors for pneumothorax include positive pressure ventilation, meconium aspiration, active resuscitation, male sex, and being larger in size [5][6][7]. Cesarean delivery [5,7] and birth outside a tertiary perinatal center [8][9][10][11] have also been suggested as risk factors for pneumothorax, but the evidence is conflicting. Furthermore, the majority of previous studies of pneumothorax were limited to single centers with small sample sizes and low statistical power [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These results in VLBW infants are congruent with prior reports on neonatal transport. 4,10,14 Among the individual TRIPS variables, the impact on transport outcomes for VLBW infants appears to be related to temperature regulation; accounting for a change in the physiologic status of 79% of the study infants. Longer transport durations in neonates may result in inadequate control of body temperatures, which can potentially increase the morbidity and mortality in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies on transport of pediatric trauma patients in population-sparse areas have shown that longer duration of transport is associated with higher mortality and morbidity. 8,9 In a recent study of 208 infants with transient tachypnea of newborn (TTN), Karagol et al 10 showed that long-distance land-based transport in neonates with TTN increases the severity of illness.…”
mentioning
confidence: 99%
“…The recognized risks of transferring critically ill patients by ambulance or air transport are associated with a high incidence of serious hemodynamic or respiratory instability. 1,2 Four scores are used to assess transported infants, each with inherent advantages and disadvantages. [3][4][5][6] The Transport Risk Index of Physiologic Stability (TRIPS) 5 was originally designed to assess infant status before and after transport.…”
mentioning
confidence: 99%